PENERAPAN SEKOLAH RAMAH ANAK DALAM MENINGKATKAN KARAKTER ANAK DI TK AL HIKMAH - Rosida Rosida; Miftakhul Jannah; Yes Matheus Lasarus Malaikosa (CV. ADIBA AISHA AMIRA, 2024)
This study aims to explore the implementation of child-friendly schools in enhancing the character of early childhood at TK Al Hikmah. The research method employed is a qualitative approach with a case study design. The subjects in this study are early childhood students at TK Al Hikmah Ketapang Banyuwangi. Data collection techniques include observation, interviews, and literature review. The results indicate that the implementation of child-friendly schools at TK Al Hikmah has led to significant changes in school facilities and infrastructure, active participation of students in school activities, improved communication between teachers, students, and parents, as well as the formation of better character in students. Furthermore, child- friendly schools have also positively impacted the academic aspects of students, with increased motivation to learn and academic achievements. Despite facing challenges such as resistance from various parties and resource limitations, collaborative and sustainable approaches have proven effective in overcoming these obstacles. In conclusion, the implementation of child-friendly schools can contribute to shaping a generation with noble, disciplined, and responsible character, with support from all stakeholders, including schools, families, and communities.